Trends against receiving the Corona vaccine by gender and experienceBy university students - Lina Hassan Muhammad; Omar Ibrahim Azeez (Zanco Journal of Humanity Sciences)
The aim of this research is to measure the level of all attitudes towards receiving vaccination among Salahaddin University students, and the differences according to gender variables (male - female) and according to specialization variables (scientific - human). The sample consisted of (380) male and female students, of whom 142 were male and 238 were female. The scale that the researchers prepared to measure attitudes to receiving the coronavirus vaccine based on the scale (Aziz, 2020) was extracted for the virtual honesty scale, and its face value was (0.80) and more, and the stability calculation was (0.80), which is a high level. After applying the scale to the research sample, the researchers found that the level of attitude towards vaccination is high among students, and there are statistically significant differences in the level of attitude towards vaccination according to the gender variable (male - female) and in favor of the female. And there were no statistically significant differences in the level of orientation towards vaccination according to the variable of specialization (scientific - human). In light of the results, the researchers presented a set of recommendations and proposals.